Biological control of sheath blight of rice by Trichoderma harzianum using different delivery systems - RAJBIR SINGH, LAKSHMI TEWARI* and (Indian Phytopathology, 2005)
Differential mode of application (delivery system) of Trichoderma harzianum influenced the biological control potential of the bioagent against sheath blight of rice under both glasshouse and field conditions. Disease severity and incidence were significantly reduced by application of bioagent in all cases except for soil treatment under glasshouse conditions. Among different delivery systems evaluated, a mixed mode of application comprising of soil treatment, root dipping and foliar spray altogether, was found most effective under glasshouse conditions showing significantly reduced values for disease severity (29.07per cent) and disease incidence (58.40 per cent) as compared to other treatments. For field application, foliar spray was found superior showing significantly reduced disease severity (40.82 per cent) as compared to other treatments. Grain yield was significantly increased due to bioagent application using any mode under field conditions. Results were more pronounced after second spray at 30 days than the first spray at 15 days. However, among different delivery systems evaluated, soil treatment was found least effective for control of sheath blight of rice under both glass house and field conditions.